Comprehensive wound healing using ETN@Fe7S8 complex by positively regulating multiple programmed phases - Mengxia Chen; Ting Liu; Xiaonan Wang; Lizeng Gao; Yunqing Cheng; Jing Jiang; Jinhua Zhang (Journal of Nanobiotechnology)
Abstract Wound healing requires coordinated progression through multiple programmed phases including hemostasis, infection control, inflammatory resolution, proliferation, and tissue remodeling. Many nanomaterials have shown great potential to promote wound healing, however, most of them only address partial aspects of these processes, making a recovery hard with adequate effects. In this study, we prepared a complex of nano-iron sulfide integrated with erythrocyte-templated nanozyme (ETN) (ETN@Fe7S8) for comprehensive treatment of wounds. Firstly, ETN served as a mediator to confine iron sulfide to form Fe7S8 nanocomposite in a solvothermal reaction. Secondly, the ETN@Fe7S8 demonstrated bactericidal effects against methicillin-resistant Staphylococcus aureus (MRSA) by releasing ferrous iron and polysulfide to induce ferroptosis-like cell death. Thirdly, ferrous iron along with polysulfide exerted anti-inflammatory effects by inhibiting the activation of the NF-κB signaling pathway, while the polysulfide also contributed to angiogenesis by promoting the activation of vascular endothelial growth factor A (VEGFA), initiated phosphorylation-mediated activation of the PI3K/AKT signaling pathway, a master regulatory cascade governing endothelial cell survival, migration, and angiogenesis. When employed for wound, ETN@Fe7S8 showed the ability to prevent infection, reduce inflammation, promote angiogenesis, enhance cell proliferation, and remodel keratinocytes. Along with the hemostatic effect, ETN@Fe7S8 thus performed comprehensive effects for wound healing in the whole recovery stages. Therefore, our findings provide a multifunctional candidate of ETN and nano-iron sulfide complex which is capable of regulating and promoting wound healing. Graphical Abstract